Can an electronic textbooks be part of K-12 education?: Challenges, technological solutions and open issues - Lee, Jasmine Hee Jeong; Messom, Chris; Yau, Alvin Kok-Lim * (TOJET: The Turkish Online Journal of Educational Technology, 2013)
An electronic textbook (e-Textbook) is a digitized (or electronic) form of textbook, which normally needs an endorsement by the national or state government when it is used in the K-12 education system. E-Textbooks have been envisioned to replace existing paper-based textbooks due to its educational advantages. Hence, it is of paramount importance for the relevant parties (i.e. national and state governments, or school districts) to draw a comprehensive roadmap of technologies necessary for the successful adoption of e-Textbooks nationwide. This paper provides a brief overview of e-Textbooks and subsequently an extensive discussion on challenges associated with e-Textbooks in the pursuit of replacing traditional textbooks with e-Textbooks. This paper further provides an extensive review on how the challenges have been approached using existing e-Textbook technologies, such as multi-touch technology, e-Paper, Web 2.0 and cloud computing. Literature review and interview have been conducted to identify the challenges of e Textbooks implementation in terms of e-Textbook usage levels and the reasons of its refusal. There were 180 students and 20 academic staff participated as a sample for interviews. Eight categories of key challenges were identified. Subsequently, assessment was performed on how the evolving e-Textbook technology has been applied to address the key challenges and problems. This article aims to provide a strong foundation for further investigations in e-Textbooks for successful adoption of e-Textbooks in school education.